Autotaxin is a novel target of microRNA‐101‐3p. Issue 4 (1st March 2019) - Wang, Yuqin; Lyu, Lin; Zhang, Xiaotian; Zhang, Junjie
Abstract : Autotaxin (ATX), a vital enzyme that generates lysophosphatidic acid (LPA), affects many biological processes, including tumorigenesis, via the ATX–LPA axis. In this study, we demonstrate that microRNA‐101‐3p (miR‐101‐3p), a well‐known tumor suppressor, downregulates ATX expression at the posttranscriptional level. We found that miR‐101‐3p inhibits ATX regulation by directly targeting a conserved sequence in the ATX mRNA 3′UTR. Moreover, we observed an inverse correlation between ATX and miR‐101‐3p levels in various types of cancer cells. ATX is highly expressed in several human cancers. Here, we verified that ATX expression is significantly inhibited by miR‐101‐3p in U87 and HCT116 cells. ATX downregulation contributed to the suppression of migration, invasion, and proliferation mediated by miR‐101‐3p; furthermore, the tumor‐suppressing activity of miR‐101‐3p was partially reduced by the addition of LPA in U87 cells. Our data suggest that ATX is a novel target of miR‐101‐3p. Abstract : Autotaxin (ATX) is a key enzyme in the production of lysophosphatidic acid (LPA). The ATX–LPA axis is involved in oncogenesis and cancer progression. Here, we identified ATX as a novel target of microRNA‐101‐3p (miR‐101‐3p). miR‐101‐3p downregulates the expression of ATX by directly targeting a conserved sequence in ATX mRNA 3′UTR, leading to the suppression of cancer cell migration, invasion, and proliferation.